UTAUT2 Approach to the Effect of Price Value, Social Influence, and Trust on Robux Purchasing Decisions through Gamepass on the Roblox Platform - Valentino Chandra; William Wendy Ary (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The rapid growth of the digital gaming industry and the increasing prevalence of microtransactions within metaverse ecosystems have made the understanding of users’ purchase behavior an increasingly important issue, particularly on platforms such as Roblox that rely on Robux and Gamepass as primary monetization instruments. This study aims to analyze the effects of price value, social influence, and trust on users’ purchase decisions of Robux through Gamepass on the Roblox platform using the UTAUT2 model. The main research question focuses on the extent to which these three factors influence users’ purchase decisions. The study employs a quantitative explanatory research design using a survey method, in which data were collected through a Likert-scale questionnaire and analyzed using inferential statistical techniques. The results indicate that price value, social influence, and trust have positive and significant effects on purchase decisions of Robux through Gamepass. These findings suggest that purchase decisions are not solely determined by economic value considerations, but are also influenced by community social dynamics and the level of trust in the platform’s security and reliability. This study contributes to the digital consumer behavior literature by extending the application of UTAUT2 to the context of online gaming and virtual economies. Overall, the findings emphasize the importance of integrating rational, social, and psychological aspects in understanding digital purchase decisions and provide opportunities for future research to explore additional variables and more diverse methodological approaches.